Políticas públicas de leitura e a constituição simbólica do mundo representado: o direito à literatura indígena no PNLD literário - Barros Júnior, José Paulo Alexandre de (2023)
This dissertation seeks to analyze the regime of symbolic representation of indigenous/original people in the policies and guidelines of the State that founded the rumors of book programs in Brazil, until the constitution of the current National Program of Literary Didactic Books (PNLD - Literário). A hypothesis outlined in the construction of this research is based on the assumption that cultural policies to promote reading have an institutional apparatus that directly influences and controls our Cultural Circuit, space that indigenous alterities are constructed, structured and mapped to the world they are represented. As a guardian of the constitutional forces that determine the protection of social organization, beliefs and indigenous traditions, it is up to the Brazilian State to defend and promote the intellectual and copyright rights of these peoples as an issue inherent to the guarantee imposed by the Brazilian Constitution of 1988. In the hope of understanding whether this right is being implemented through Brazilian institutional guidelines, we frame our methodological process in the typology of documentary research, considering as documents the entire institutional apparatus composed of laws, decrees, regulations, decrees and manuals edited by the Brazilian State, intended for the dissemination and implementation of public policies aimed at literary reading in the country through book programs. In this sense, the documentary work is theoretically supported by the perspectives of Hall (2016), Smith (2018), Amaral and Souto (2022), Danner et al. (2018, 2020, 2022), among others. On the way to the proposed objectives, we have structured this dissertation into three chapters that lead to relevant conclusions for understanding the representational dynamics constituted by these policies: 1) Imperialism finds cultural reading policies in Brazil, an area of excellence for its constitution symbolic domain, having in mind the fragility of State programs in their constant discontinuities and ruptures, which seek to meet the demands of international agendas to the detriment of the emancipatory formation of the Brazilian nation; 2) Once engendered in the cultural policies of the Brazilian State, the intervening character of imperialism can be seen in the fabric of subjectivities involved that would meet its ideal model of society, based on the castration and symbolic extermination of the original peoples; 3) The logic of the essay approaches the typical censorship policies of the Brazilian State in authoritarian contexts, which reinforces the need to strengthen our cultural policies aimed at literary reading, so that the current book programs belong to the State that we protect the right to the Cultural Enhancement of Brazil, which includes the Right to Indigenous Literature as a human need for the formation of the Brazilian people.